Granzyme K mediates IL-23-dependent inflammation and keratinocyte proliferation in psoriasis - Richardson, Katlyn C.; Aubert, Alexandre; Turner, Christopher T.; Nabai, Layla; Hiroyasu, Sho; Pawluk, Megan A.; Cederberg, Rachel A.; Zhao, Hongyan; Jung, Karen; Burleigh, Angela; Crawford, Richard I.; Granville, David J. (Frontiers in Immunology, 2024)
Psoriasis is an inflammatory disease with systemic manifestations that most commonly presents as itchy, erythematous, scaly plaques on extensor surfaces. Activation of the IL-23/IL-17 pro-inflammatory signaling pathway is a hallmark of psoriasis and its inhibition is key to clinical management. Granzyme K (GzmK) is an immune cell-secreted serine protease elevated in inflammatory and proliferative skin conditions. In the present study, human psoriasis lesions exhibited elevated GzmK levels compared to non-lesional psoriasis and healthy control skin. In an established murine model of imiquimod (IMQ)-induced psoriasis, genetic loss of GzmK significantly reduced disease severity, as determined by delayed plaque formation, decreased erythema and desquamation, reduced epidermal thickness, and inflammatory infiltrate. Molecular characterization in vitro revealed that GzmK contributed to macrophage secretion of IL-23 as well as PAR-1-dependent keratinocyte proliferation. These findings demonstrate that GzmK enhances IL-23-driven inflammation as well as keratinocyte proliferation to exacerbate psoriasis severity.